Globalization and regionalization: ¿Fractured by pandemia? - Álvarez Béjar, Alejandro (Posgrados de la División de Ciencias Económica Administrativas, 2021)
The COVID19 pandemic brought serious economic, political, cultural and social costs that aggravated pre-existing inequalities, evidencing the need for multilateral actions, precisely because neoliberal formulas exhibited their failure with the deficiencies of the health systems, housing conditions, educational systems, pensions, loss of jobs, income and life chances after “social distancing”. Adding up the dynamics of technological change, we will experience other mutations: an eventual relative deglobalization, settling the shift from the Atlantic to the Pacific, with China as a rising power. And a deep global regionalization, in two ways: one, the emphasis on national responses to the pandemic (which can affect food production, industries such as pharmaceuticals, materials for the health sector, but also telecommunications, energy and utilities); two, due to the eventual relocation of global industrial supply chains in anticipation of major disruptions due to the pandemic, for reasons of national security or for environmental reasons. Regionalization, led by large technology companies, will not be fully global because they operate with different standards and regulations, data rights regimes, tensions between individual rights and incentives for innovation, international discrepancies.